UAV Fuel Preferences for Future Cities - Celik, Kubra; Eren, Haluk (Ieee, 2018)
Today, the infrastructure of land unmanned transportation has been developed in some countries, but UAV usage is very new for civil package transportation. Long endurance flights are possible with developing energy systems, fuel applications, and refueling options. The choice of fuel and refueling systems are important for UAV's proper working conditions. In our study, the different fuel systems for UAVs are evaluated, and electric vehicle based battery systems are proposed for UAV's for civil package transportations and smart city applications. This work mentions about the other studies conducted in recent decade. Consequently, public authorities may develop their policies considering highlighted points in the present and previous studies. The right transport strategies, national and international regulations for UAVs can help to produce relevant technology infrastructures.
6th International Istanbul Smart Grids and Cities Congress and Fair (ICSG) -- APR 25-26, 2018 -- Istanbul, TURKEY
Keywords: UAV; Fuels; Li-polymer Battery; Power Management; Smart City Integration